Cultivating Culture: Youth Food Movement in the Taos Pueblo Native American Community - Jordan C Thomas (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2017)
A large number of studies have emerged in recent years regarding the social effects of local food systems. They have been shown to bolster local economies, increase general health, and even decrease crime rates. This study analyzes the effect of local food systems in the Taos Pueblo community, and how and why they create positive farming ideologies. A proposed covert effect may correlate to developments of positive ideologies towards native heritage, which would imply that local food systems can help to preserve indigenous language and culture. To study these trends I moved to Taos, New Mexico with my research partner, where we immersed ourselves in a Tiwa Pueblo youth food movement. Throughout three months of intensive fieldwork, we gathered interview data and engaged with participant observation in the community in order to elicit localized perceptions of native culture and local food cultivation. We interviewed sixteen community members and accumulated over twenty hours of interview data. Combining the interview data with my participant observation experiences, I found mutually reciprocal relationships between positive community ethics of food cultivation and positive ethics of native identity and heritage, while also gaining insight into the primary manners in which the Pueblo youth create their traditional farming ideologies, and why. This study is arranged here in a narrative literary style meant to appeal to a broad audience, without losing its academic rigor. Ideally, the findings will shed light on yet another social effect of local food systems, which could be capitalized upon when dealing with future development issues. This study could also encourage more quantitative data gathering at Taos Pueblo.
Keywords: Culture; farming; indigenous; youth; anthropology